Analisis Pembinaan Karakter Disiplin Siswa Melalui Metode Reward And Punishment di Madrasah Ibtidaiyah Berbasis Islamic Boarding School - Hidayat, Wahyu; Hidayat, Nur (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2024)
The study of character is a problem that occurs a lot. The formation of disciplinary character can be influenced by environmental factors, as well as family. The importance of efforts to foster discipline character from an early age through Reward and Punishment is one of the keys to students having good character, especially discipline, and inherent in themselves. This research is qualitative research with a phenomenological approach. The subject of this study was a student of At-Tariq Dormitory MI Al Ma'had An Nur Ngrukem Bantul. This research data was collected through interviews, observation, and documentation. Data analysis of this study used the concept of Miles and Huberman analysis. The validity of this data is used to check through extended participation, persistence of observation, and triangulation of methods. The results of this study are Reward for students in activities including Reward early grade students in order to perform fardhu prayers, reward students in tahfidzul Qur'an, and reward students in order in dormitory. While Punishment for students includes a series of penalties that have been determined for violations of the rules that apply in the dormitory.